Health Vulnerability Model for Latinx Sexual and Gender Minorities: Typologies with Socioeconomic Stability, Health Care Access, and Social Characteristics Indicators - Alice Ma; Jennifer Toller Erausquin; Amanda E. Tanner; Eunyoung Y. Song; Manuel Garcia; Jorge Alonzo; Lilli Mann-Jackson; Scott D. Rhodes (New Prairie Press, 2021)
Vulnerability can undermine positive health outcomes and challenge healthcare services access. However, to date, vulnerable populations research has been limited by overly broad definitions, lack of clear indicators, and failure to explore subtypes of vulnerability. Informed by literature and theory, this analysis used a specific operationalization of health vulnerability to identify typologies among a sample of Latinx sexual and gender minorities. We analyzed baseline data from Latinx sexual and gender minorities (N = 186) recruited for a community-based HIV intervention. We performed latent class analysis to operationalize vulnerability using eight socioeconomic stability, health care access, and social characteristics indicators. We identified three typologies of vulnerability from our sample: Low Education and High Social Support (63.4% of sample), High Education and Year-round Employment (18.8%), and High Education and High Discrimination (17.7%). Using specific indicators produced more nuanced vulnerability typologies which, after further testing, can assist in informing tailored health promotion interventions.